Fall Risk in Community Dwelling Elderly Cancer Survivors—A Predictive Model for Gerontological Nurses - Spoelstra, Sandra (J Gerontol Nurs, 2010)
The aim of this predictive study was to test a structural model to establish predictors of fall risk. An aging and nursing model of care was synthesized and used to examine 6912 older adult participants who are low income, using the Minimum Data Set in a community setting in the Midwest. Data analysis established relationships among age, race, a history of a previous fall, depression, pain, and ADLs, IADLs, incontinence, vision, and cognitive status. Factors leading to fall risk can direct nursing activities that have the potential to prevent falls, improving quality of life.